Morbidity and mortality in motor neuron disease: comparison with multiple sclerosis and Parkinson's disease: age and sex specific rates and cohort analyses. Issue 4 (April 1985) - Li, T M; Swash, M; Alberman, E
Abstract : The cause of motor neuron disease (MND) remains unknown although recent reports have suggested a possible rise in mortality rate. The present account describes age-specific patterns in morbidity rate and cross-sectional and cohort analyses of mortality rate, and compares these with those in multiple sclerosis and Parkinson's disease. First hospital admission rate for motor neuron disease (a proxy for incidence rates) rose steadily with age in males and females until the age of 75 years or more, but then fell, but only in females. This irregular pattern suggested the possibility of an environmental effect on certain older birth cohorts. The validity of the results was supported by a similar pattern in the two hospital regional authorities studied and the difference between this pattern and that found in multiple sclerosis and Parkinson's disease. Age-specific mortality rates of motor neuron disease between 15 and 64 years for males and females in England and Wales from 1940 to 1982 rose steadily with age. Mortality rates after the age of 65 fell in all female cohorts studied, but only in the earlier male cohorts. Unlike Parkinson's disease there was no strong birth cohort effect. However an analysis of Office of Population Censuses and Surveys (Registrar General) reports has revealed a slight increase in the age-specific mortality rate in both males and females aged 65 and over for successive birth cohorts born since 1900. Neither changes in ICD coding or in diagnostic habits could account for this pattern, which differed from that seen in Parkinson's disease. No such effect was seen in multiple sclerosis.